MODEL PENINGKATAN KUALITAS SDM DESA BERDASARKAN SPIRITUALITY WORK LIFE BALANCE - Sutrisna, Arga; Pratiwi, Laras; Putri Lestari, Suci (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This research uses a mixed approach, namely a qualitative and quantitative approach. In terms of objectives, this type of research is associative descriptive. This research aims to describe and analyze in depth (in depth analysis) the quality of human resources in Pananjung Village and analyze the extent to which Spirituality Worklife Balance influences the quality of human resources. The results of this research show that the magnitude of the influence of emotional intelligence and Spirituality Worklife Balance on improving the quality of human resources is in the moderate category. The magnitude of the influence of emotional intelligence on Spirituality Worklife Balance is in the moderate category. Emotional intelligence has a significant influence on the quality of human resources. Emotional intelligence has a significant influence on Spirituality Worklife Balance. Spirituality Worklife Balance has a significant influence on HR Quality. Emotional intelligence has a significant indirect influence on the quality of human resources through Spirituality Worklife Balance. Spirituality Worklife Balance significantly acts as a variable that mediates the indirect influence of emotional intelligence on the quality of human resources.